Minto 1932: The Origins and Significance of a New Brunswick Labour Landmark - Frank, David (Acadiensis, 2007)
This study considers the significance of the the death of three children and two adults in a local mine shaft in Minto, New Brunswick, on 28 July 1932 and of the act of commemoration 50 years later. It examines the impact of the disaster on individuals, families and the community as well as its influence on the adoption of mine safety laws and the administration of workers’ compensation. A relatively obscure episode in the larger history of casualties of the industrial revolution, this event contributed to the recognition of New Brunswick workers and their place in provincial society. Résumé Cette étude s’intéresse à l’importance qu’a revêtue la mort de trois enfants et de deux adultes survenue le 28 juillet 1932 dans un puits de mine à Minto, au Nouveau-Brunswick, et au geste de commémoration dont elle fut l’objet 50 ans plus tard. Elle examine l’impact du désastre sur les individus, les familles et la communauté, ainsi que son influence sur l’adoption de lois concernant la sécurité dans les mines et sur la gestion de l’indemnisation des accidentés du travail. Cet événement, épisode relativement obscur dans l’histoire plus large des pertes de vies humaines lors de la révolution industrielle, contribua à la reconnaissance des travailleurs du Nouveau-Brunswick et de leur place dans la société provinciale.